2015
DOI: 10.3390/ijms16022678
|View full text |Cite
|
Sign up to set email alerts
|

Novel Localization of Peripherin 2, the Photoreceptor-Specific Retinal Degeneration Slow Protein, in Retinal Pigment Epithelium

Abstract: Retinal pigment epithelium (RPE) builds the outer blood-retinal barrier of the eye. Since one typical feature of the autoimmune disease, equine recurrent uveitis (ERU), is the breakdown of this barrier, we recently performed comparative analysis of healthy and uveitic RPE. We identified for the first time peripherin 2, which is responsible for visual perception and retina development, to be localized in RPE. The purpose of this study was therefore to validate our findings by characterizing the expression patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The retinal pigment epithelium (RPE), situated on the outer side of the retina, is a monolayer of cells connected by tight junctions with important functions for the visual system [ 1 ]. ARPE-19, a spontaneously arising cell line of RPE, has been extensively used in the past decades to investigate the role of this cell layer in the pathogenesis of a number of diseases including age-related macular degeneration (AMD), vitreoretinopathy, and uveitis [ 2 5 ]. The major inflammatory cytokines produced by ARPE-19 in response to various stimuli are interleukin-6 (IL-6), interleukin-8 (CXCL8, IL-8), and monocyte chemoattractant protein-1 (CCL2, MCP-1) [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The retinal pigment epithelium (RPE), situated on the outer side of the retina, is a monolayer of cells connected by tight junctions with important functions for the visual system [ 1 ]. ARPE-19, a spontaneously arising cell line of RPE, has been extensively used in the past decades to investigate the role of this cell layer in the pathogenesis of a number of diseases including age-related macular degeneration (AMD), vitreoretinopathy, and uveitis [ 2 5 ]. The major inflammatory cytokines produced by ARPE-19 in response to various stimuli are interleukin-6 (IL-6), interleukin-8 (CXCL8, IL-8), and monocyte chemoattractant protein-1 (CCL2, MCP-1) [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, horses with ERU display a distinctly changed RPE membrane protein repertoire in ERU ( 91 ). A significant decrease of peripherin 2, a protein that is associated with membrane fusion processes, in RPE cells of ERU horses is thought to provoke disruption of the cell-to-cell junctions which are physiolocically maintained through these cells ( 92 ), which in turn points to increased permeability of the outer BRB. As also hypothesized for PEDF ( 19 , 20 , 82 ), this might promote integrity loss of the BRB.…”
Section: Target Organmentioning
confidence: 99%
“…As also hypothesized for PEDF ( 19 , 20 , 82 ), this might promote integrity loss of the BRB. Although loss of barrier function of the BRB and leukocyte infiltration in course of ERU is evident ( 4 , 27 , 91 , 92 ), the exact chronological order of these events is still not completely clear. Integrity loss of the BRB may occur either as an initial process which subsequently facilitates migration of peripheral immune cells into the eye, or as a secondary effect in response to leukocyte recruitment.…”
Section: Target Organmentioning
confidence: 99%
“…In any case, some of the experiments carried out with regenerated Rho point to the fact that the presence of chromophore may not be determinant for the interaction. And despite that some authors suggest more prominent interactions of Rho with guanylate cyclase 1 in comparison with Rho and Prph2 (Pearring, Spencer, Lieu, & Arshavsky, 2015), a novel co-localization of Prph2 and Rho in RPE cells also supports the existence of this protein complex (Uhl et al, 2015).…”
Section: Rho-prph2 Interaction Analysismentioning
confidence: 90%
“…In this way, the rim region of the disk membrane has a curvature that is facilitated by the presence of Prph2 (Gurevich & Gurevich, 2015) Recent research provided new insights on this protein showing that Prph2 can interact with Rho, while at the same time demonstrated that Rho is also located in the rim region of the disks (Becirovic et al, 2014) despite previous articles that suggested a compartmental Rho distribution (in the centre) and Prph2 (in the rims) of the ROS disks membranes (Buzhynskyy, Salesse, & Scheuring, 2011). Moreover, Prph2 has also been localized in the RPE (Uhl, Amann, Hauck, & Deeg, 2015) 1.4 Visual signal transduction…”
Section: Peripherinmentioning
confidence: 99%